Perempuan Dalam Kumpulan Puisi Onna Ni Karya Shuntaro Tanikawa - Wirupawan, I Gede (Humanis, 2017)
This research entitles “Woman in Onna ni Collection of Poems by Shuntaro Tanikawa”. This research is aimed to find out the image of woman in Japanese society which is reflected in Onna ni  collection of poems. It also to know the poet’s view of woman contained in the poems collection. The data were analyzed using descriptive analysis. Theory used is feminist literary criticism by Sugihastuti (2005) and semiotic theory by Peirce in Pradopo (2007) as supporting theory. The result can be concluded woman image in Onna ni collection of poems can be seen from physical aspect, psychic aspect and social aspect. Physical aspect of woman is adult woman who has a soft aroma, soft body and big clear eyes there are beautiful woman criteria according Japanese people. Woman psychic aspect is woman who has sensitive emotional and has good attitudes and behavior.From the Social aspect, woman is who are not only plays a role in the domestic environment relating to woman as parent are mother , woman in kinship as a wife, and a woman in personal relationship with her lover, but also the relationship of woman in society concerning the interaction of women with other individuals outside the home and in the workplace.From the view of the poet, the poet of male feminists give the view that women are creatures who have love and compassion, work and responsible, strong, character, confident, interesting, creative, and insightful.
Keywords: , character, confident, interesting